2001
DOI: 10.1016/s0925-5214(00)00189-7
|View full text |Cite
|
Sign up to set email alerts
|

1-MCP blocks ethylene-induced petal abscission of Pelargonium peltatum but the effect is transient

Abstract: Continual exposure to 1.5 ml l − 1 ethylene caused 100% petal abscission within 2 h from detached flowers of Pelargonium peltatum (L.) 'Pink Blizzard' (ivy geranium) harvested just after the stigmatic lobes had separated. When flowering plants were first pretreated for 2 h with 1 ml l − 1 1-MCP, ethylene-induced petal abscission was completely inhibited. However, the effect was transient, since percent abscission increased with time after 1-MCP treatment. Based on percent abscission from detached flowers after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 19 publications
6
46
0
1
Order By: Relevance
“…Delays in floral senescence using 1-MCP were observed in many species, such as alpinias (Mattiuz, 2005), roses Mattiuz, 2010), oriental lilies (Celikel et al, 2002), geraniums (Cameron;Reid, 2001;Jones et al, 2001) and orchids (Moraes et al, 2007). Serek, Sisler and Reid (1995) observed that the use of 1-MCP increased the vase life of Alstroemeria cut flowers.…”
Section: Galati V C Et Almentioning
confidence: 99%
“…Delays in floral senescence using 1-MCP were observed in many species, such as alpinias (Mattiuz, 2005), roses Mattiuz, 2010), oriental lilies (Celikel et al, 2002), geraniums (Cameron;Reid, 2001;Jones et al, 2001) and orchids (Moraes et al, 2007). Serek, Sisler and Reid (1995) observed that the use of 1-MCP increased the vase life of Alstroemeria cut flowers.…”
Section: Galati V C Et Almentioning
confidence: 99%
“…CAT activity was pronounced at 20 mg L -1 and 40 mg L risks for human health and environment. Although 1-MCP blocks ethylene-induced petal abscission of Pelargonium, the effect is impermanent (Cameron and Reid, 2001;Damunupola and Joyce, 2006). The development of nanotechnology in physiology and biochemistry has expanded the application area of nanomaterials in different fields due to their unique characteristics (e.g., large surface area-to-volume ratio, ability to engineer electron exchange, and highly surface reactive capabilities) (Scrinis and Lyons, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of C. uncinatum cultivars with the ethylene binding inhibitors silver thiosulphate (STS) liquid and 1-methylcyclopropene (1-MCP) gas reduced floral organ abscission (Joyce, 1988(Joyce, , 1989Serek et al, 1995;Macnish et al, 2000a, b). However, concern over the disposal of silver-containing waste solution into the environment has prompted legislators to restrict the use of STS on ornamentals (Cameron and Reid, 2001). On the other hand, a single 1-MCP treatment may only protect C. uncinatum flowers against ethylene for 2 to 4 days (Macnish et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%